2005
DOI: 10.1007/s00330-005-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Observation of contrast enhancement in the cochlear fluid space of healthy subjects using a 3D-FLAIR sequence at 3 Tesla

Abstract: In animals, the enhancement of perilymph in the cochlea has been reported using 1.25 mmol/kg of Gd-DTPA, allowing the separate visualisation of perilymph and endolymph for the diagnosis of Meniere's disease. The purpose of this study was three-fold: (1) to determine the optimal timing for detecting cochlear fluid enhancement using 3D-FLAIR (fluid-attenuated inversion recovery) after intravenous administration of 0.1 mmol/kg of Gd-DTPA in healthy human subjects; (2) to examine the reliability of enhancement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 13 publications
(23 reference statements)
2
74
1
2
Order By: Relevance
“…Furthermore, another previous study revealed the cochlear fluid enhancement 4 hours after singledose IV gadolinium injection on 3D-FLAIR in healthy subjects. 22 Therefore, the cochlear enhancement should be observed 4 hours after double-dose IV gadolinium injection in healthy people, though further investigation is required to clarify this matter because the number of controls in the present study was too small for statistical analysis.…”
Section: Figmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, another previous study revealed the cochlear fluid enhancement 4 hours after singledose IV gadolinium injection on 3D-FLAIR in healthy subjects. 22 Therefore, the cochlear enhancement should be observed 4 hours after double-dose IV gadolinium injection in healthy people, though further investigation is required to clarify this matter because the number of controls in the present study was too small for statistical analysis.…”
Section: Figmentioning
confidence: 83%
“…28 The reports describing intratympanic gadolinium injection in human subjects have been published from several institutions, including ours, [11][12][13][14][15][23][24][25][29][30][31] and no marked side effects in the inner ear relating to intratympanic gadolinium injection have been reported on clinical application at present, to the best of our knowledge. In addition, intravenously administered gadolinium has been reported to infiltrate inner ear perilymph, 16,17,22,23 and no marked side effects in the inner ear relating to IV gadolinium injection have been reported in the clinical application at present. Therefore, gadolinium agent use in the clinical setting appears safe for inner ear imaging, but future study requires continued vigilance regarding the small possibility of side effects.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…Four hours after intravenous administration of Gd-DTPA in healthy human volunteers, a slight increase in signal intensity was noted in the labyrinth. 8 However, probably because of a gadolinium concentration that was too low in the perilymphatic space, differentiation between the endolymphatic and perilymphatic space was not achieved. Intratympanic injection of Gd-DTPA and the application of 3D-FLAIR at 3T made the visualization of endolymphatic hydrops possible in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…This can be done with triple-dose intravenous injection with delayed scanning (optimal at 4-8 hours), allowing contrast to diffuse from the CSF to the perilymph 11 or by introduction of dilute gadolinium into the middle ear with diffusion of contrast into the perilymph across the round window membrane. 12 Both these techniques would be difficult to introduce into clinical practice for obvious reasons.…”
Section: Discussionmentioning
confidence: 99%